Isolation and characterization of a Siphoviridae phage infecting Bacillus megaterium from a heavily trafficked holy site in Saudi Arabia - Othman, B A; Askora, Ahmed; Abo-Senna, Amel S M (Folia microbiologica, 2015)
In this study, we isolated and characterized a Siphoviridae phage isolated from the vicinity of a religious structure (Kaaba) in Makkah, Saudi Arabia. The phage was designated as φBM and characterized using transmission electron microscopy, restriction digestion of its DNA, and host range. Electron micrograph indicated that φBM phage has an icosahedral head with diameter of about 65 ± 5 nm and long, non-contractile tail with length of about 300 ± 10 nm and width of about 17 ± 2 nm, respectively. On the basis of the φBM phage morphology, we thus propose that φBM represents a member of Siphoviridae phages. The φBM phage was shown to be able to infect Bacillus megaterium and two other Bacillus species and has no effect on other tested bacteria. φBM was stable over the pH range of 5-9, chloroform resistant and stable at 4 °C. A one-step growth experiment showed a latent period of about 40 min and a burst size of approximately 65 per infected cell. The purified bacteriophage appeared to consist of ten proteins. The genome size was estimated to be ∼38 kb. To our knowledge, this is the first report on the isolation of a bacteriophage from Kaaba a heavily trafficked holy site in Saudi Arabia.
Keywords: DNA, Viral; DNA virů; Siphoviridae; Hydrogen-Ion Concentration; Chloroform; Restriction Mapping; Temperature; mikrobiologie životního prostředí; Host Specificity; Saudská Arábie; Microscopy, Electron, Transmission; Bacillus megaterium; Environmental Microbiology; transmisní elektronová mikroskopie; fágy bacilů; hostitelská specificita; teplota; Microbial Viability; restrikční mapování; Saudi Arabia; chloroform; koncentrace vodíkových iontů; Bacillus Phages; mikrobiální viabilita